A Weighted Gene Co-expression Network Analysis Reveals lncRNA Abnormalities in the Peripheral Blood Associated With Ultra-High-Risk for Psychosis - Ren, Yan; Li, Wei; Liu, Sha; Li, Zhi; Wang, Jiaying; Yang, Hong; Xu, Yong (Frontiers in Psychiatry, 2020)
Objective: The primary study aim was to identify long non-coding RNA (lncRNA) abnormalities associated with ultra-high-risk (UHR) for psychosis based on a weighted gene co-expression network analysis. Methods: Fourteen treatment-seeking patients with UHR who never received psychiatric medication and eighteen typically developing controls matched with respect to gender and age were recruited from the Department of Psychiatry at the First Hospital of Shanxi Medical University. Patients were operationalized by the structured interview for prodromal syndromes (SIPS). RNA was extracted from blood samples for analyses of differentially expressed lncRNAs. The functions of lncRNAs and associated mRNAs were evaluated. Changes in the characteristics of lncRNA–mRNA co-expression networks in UHR were evaluated. A canonical correlation analysis was used to determine relationships between hub lncRNAs and hub mRNAs. Additionally, diagnostic biomarkers for the precursory stage of schizophrenia were identified. Results: We identified 12 lncRNA co-expression modules by WGCNA. Two modules were strongly associated with UHR. In addition, we detected 11 mRNA co-expression network modules, two of which were highly correlated with UHR. A functional enrichment analysis showed that mRNAs were mainly related to inflammation and immune regulation. Correlations between hub lncRNAs and hub mRNAs were verified by a canonical correlation analysis. Conclusion: We identified novel lncRNA modules related to UHR. These results contribute to our understanding of the molecular basis of UHR from the perspective of systems biology and provide a theoretical basis for early intervention in the assumed development of schizophrenia.